Morbidity-mortality and performance evaluation of Brahman calves from in vitro embryo production - Pimenta-Oliveira, Andreza [UNESP]; Oliveira-Filho, Jose P. [UNESP]; Dias, Adriano [UNESP]; Goncalves, Roberto C. [UNESP] (Biomed Central Ltd., 2011)
Background: The use of bovine in vitro embryo production (IVP) increases the reproductive potential of genetically superior cows, enabling a larger scale of embryo production when compared with other biotechnologies. However, deleterious effects such as abnormal fetal growth, longer gestation period, increased birth weight, abortion, preterm birth and higher rates of neonatal mortality have been attributed to IVP. The aim of this study was to compare the influence of in vitro embryo production and artificial insemination (AI) on gestation length, complications with birth, birth weight, method of feeding colostrum, passive transfer of immunity, morbidity-mortality, and performance in Brahman calves.Results: Whilst gestation length and birth weight were significantly increased in IVP-derived calves, no difference in weaning weight was observed between groups. The passive transfer of immunity (PT), was assessed in IVP (n = 80) and AI (n = 20) groups 24 hours after birth by determination of gamma-glutamyl transferase (GGT) and gammaglobulin activity as well as by quantification of the concentration of total protein in serum. No differences in passive transfer or incidences of dystocia and diseases at weaning were observed between groups. Birth weight, method of feeding colostrum and dystocia were not correlated with PT in either group.Conclusions: In this study, in vitro embryo production did not affect the health status, development, or passive transfer of immunity in Brahman calves.